Q. 245.0( 1 Vote )

Mark the correct A. 0

B. pq

C.

D.

Answer :

Let the first term be a and the common ratio be r.


According to the question,


am+n = p.


am-n = q.


an = arn-1


am+n = a.rm+n-1


am-n = a.rm-n-1


a.rm+n-1 = p.


a.rm-n-1 = n.


Multiplying above two equations we get


a2r(m+n-1+(m-n-1) = a2r(2m-2)


a2r(2m-2) = p.q


(ar)2(m-1) = p.q


arm-1 =√p.q


Mth term is given by a.rm-1


arm-1 =√p.q

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

The product of thRD Sharma - Mathematics

Express <imRS Aggarwal - Mathematics

If a, b, c are inRS Aggarwal - Mathematics

Express <imRS Aggarwal - Mathematics

Prove that RS Aggarwal - Mathematics

If a, b, c are inRS Aggarwal - Mathematics

The sum of n termRS Aggarwal - Mathematics

If a, b, c, d areRS Aggarwal - Mathematics

Evaluate :
</p
RS Aggarwal - Mathematics

The first term ofRS Aggarwal - Mathematics